Single-layer cube armoured breakwaters: Critical review and technical challenges - Filipe Vieira (2020)
Breakwater concrete armour units have been continuously evolving since the 1950s. Lower concrete consumption, increased hydraulic stability, reduced wave run-up, and easier placement techniques are the main drivers of this development. A recent innovative solution for breakwater armour, based on one of the oldest type of units available, consists of a configuration adopting a single-layer of concrete cubes placed in a regular pattern and a porosity of 0.25-0.30. This paper presents a summary of the laboratory test results available from literature in terms of hydraulic stability and wave overtopping. Studies indicate that this is a feasible solution with several advantages over other armour configurations related to the simplicity of the cube unit and placement pattern. However, there is still some degree of uncertainty in both hydraulic stability and wave overtopping estimates for a structure with this configuration where few laboratory tests have been conducted in comparison to other armour units. Furthermore, the available methods for quantification of damage are not considered adequate for use in single-layer cube armour with a regular placement pattern. This paper discusses current knowledge gaps and provides guidelines for future research.